Implementasi Integrasi Computer Vision dan Kendali PID untuk Robot Line Follower dengan Kendali Kecepatan Dinamis - Priambodo, Ardy Seto; Nasuha, Aris; Dhewa, Oktaf Agni (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
This research aims to develop a dynamic speed control system for line follower robots by integrating computer vision technology and PID control. The main challenge in controlling line follower robots is maintaining stability and speed while navigating various types of turns and complex paths. This study proposes the use of computer vision to detect paths more accurately and responsively, and PID control to dynamically adjust the robot's speed based on detected errors. The research methods involve simulating the e-puck robot in a Webots environment, developing algorithms for black line detection and error calculation, and designing the PID control system. The test results show that in Arena 1, the completion time with fixed base speed is 58.08 seconds, while with dynamic base speed it is 50.386 seconds, indicating a 13.3% reduction in completion time. In Arena 2, the completion time with fixed base speed is 71.584 seconds, while with dynamic base speed it is 66.624 seconds, indicating a 6.9% reduction in completion time. Thus, this control system is more effective in keeping the robot on the desired path, reducing deviations and improving path tracking accuracy.